Співпраця України з Радою Європи у сфері конституційного законотворення (1996 – 2010 рр.) - Гузь, Наталія Григорівна; Guz, Nataliya (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Мета роботи полягає у вивченні співпраці України та Ради Європи у сфері конституційного законотворення. У статті досліджено розвиток співпраці України з Радою Європи та з її дорадчим органом з питань конституційного права – Венеціанською комісією. The aim of the work is to study the cooperation between Ukraine and Тhe Council of Europe in the field of constitutional lawmaking during 1996 - 2010. The paper defines the first steps of cooperation between Ukraine and the Council of Europe, which took place in condition of complex political situation in the country. Research methods are the principles of objectivity and historicism, methods of analysis and synthesis, historical-comparative and historical-systematic methods. The basic aspects of cooperation between Ukraine and The European Commission "Democracy through Law" (the advisory body on constitutional law of Council of Europe) were investigated; the results of cooperation between Ukraine and the Council of Europe in the field of constitutional lawmaking were analyzed.
Сooperation between Ukraine and the Council of Europe in the field of constitutional lawmaking (1996 - 2010)
Keywords: Україна; Рада Європи; конституційне законотворення; політика; євроінтеграція; Ukraine; the Council of Europe; the constitutional law-making; policy; European integration